2014
DOI: 10.1016/j.ijscr.2014.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Popliteal lymph node metastasis of tibial osteoblastic osteosarcoma

Abstract: HighlightsLymph node metastasis of osteosarcoma, which is a rare entity.Metastatic patterns could not be clearly explained.The effects of lymph node metastasis on prognosis are also not clearly defined and further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
1
11
0
1
Order By: Relevance
“…The specific neoplasm with general aggression mainly occurs in children and adolescence, along with an incidence of approximately 4.4 per million [Mirabello et al, ]. Previous studies have suggested OS possesses relatively high metastasis, 80% of the metastases arise in lung and the others arise in bone and lymph nodes [Byun et al, ; Dirik et al, ; Yanagawa et al, ; Gutierrez et al, ]. Even though the survival rate of patients with non‐metastatic OS is improved to 60–70% due to the advances of surgical and synthetic therapeutic methods [Zhu, ], however, for OS with detectable metastases, the survival rate remains low [Wan et al, ].…”
mentioning
confidence: 99%
“…The specific neoplasm with general aggression mainly occurs in children and adolescence, along with an incidence of approximately 4.4 per million [Mirabello et al, ]. Previous studies have suggested OS possesses relatively high metastasis, 80% of the metastases arise in lung and the others arise in bone and lymph nodes [Byun et al, ; Dirik et al, ; Yanagawa et al, ; Gutierrez et al, ]. Even though the survival rate of patients with non‐metastatic OS is improved to 60–70% due to the advances of surgical and synthetic therapeutic methods [Zhu, ], however, for OS with detectable metastases, the survival rate remains low [Wan et al, ].…”
mentioning
confidence: 99%
“…OS frequently occurs in children and young adults (4). Previous studies have suggested that OS possesses high metastatic potential; ~80% of the metastases arise in bone, lung and lymph nodes (5)(6)(7). At present, OS treatment has significantly advanced, with options including chemotherapy, radiotherapy and surgery; the survival rate of patients with non-metastatic OS has improved by 60-70% (8), although the 5-year survival rate of patients with OS exhibiting lung metastasis remains low (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…There are three common histologic types of osteosarcoma: osteoblastic, where tumor cells produce large amounts of tumor osteoid; chondroblastic, where tumor cells produce chondroid (cartilage) in addition to some amount of tumor osteoid; and fibroblastic, where tumor cells are predominantly fibroblasts and can produce both collagen and tumor osteoid [ 7 ]. The disease is highly metastatic, with distant spread mostly to lungs and other sites in bone, but osteosarcoma can also metastasize to lymph nodes and intra-abdominal organs [ 8 , 9 ]. The metastatic pattern (lungs, bones, lymph nodes) is similar for dogs and humans [ 10 ].…”
Section: Introductionmentioning
confidence: 99%